Stem-nesting Hymenoptera in Irish farmland: empirical evaluation of artificial trap nests as tools for fundamental research and pollinator conservation - Stout, Jane; Bottero, Irene (My University, 2022)
Insect pollinators are suffering global declines, necessitating the evaluation and development of methods for long-term monitoring and applied field research. Accordingly, this study evaluated the use of trap nests (“bee hotels”) as tools for investigating the ecology of cavity nesting Hymenoptera within Irish agricultural landscapes. Three trap nests consisting of 110 mm diameter plastic pipe containing 100 cardboard nest tubes of varying diameter were placed at eight apple orchards and eight oilseed rape sites and left in the field for five months. Sealed nest tubes occurred at 15 of the 16 sites, and in 77% of the 48 nests. However, only 7% of the 4800 individual nest tubes were sealed, and only 4% produced cavity-nesting Hymenoptera. Three cavity nesting bee species (Hylaeus communis, Osmia bicornis, Megachile versicolor) and two solitary wasp species (Ancistrocerus trifasciatus, A. parietinus) emerged from nest tubes. There were significant differences among species in terms of emergence date and the diameter of nest tubes from which they emerged, the latter allowing the calculation of niche width and niche overlap, and informing choice of tube size in future studies/conservation efforts. Trap nests, therefore, offer a valuable tool for fundamental ecological research and a model system for investigating interactions between stem-nesting species within their wider ecological networks. The ability of trap nests to actually increase farmland pollinator abundance and diversity as part of agri-environment schemes requires additional investigation. However, used in sufficient numbers, these trap nests provide valuable biogeographical data for cavity nesting Hymenoptera and offer a viable means for long term monitoring of these species in Irish farmland.
PUBLISHED
Keywords: Bee hotels; Cavity-nesting; Potter wasps; Mason bees; Insect declines; Smart & Sustainable Planet; Agri-ecology; Agriculture Conservation; BEES; Conservation; Pollinators